Diagnosing dysplasia in Barrett's oesophagus still requires Seattle protocol biopsy in the era of modern video endoscopy: results from a tertiary centre Barrett's dysplasia database. (2nd January 2020) - Nachiappan, Arun; Ragunath, Krish; Card, Timothy; Kaye, Philip
Abstract: Objectives: The role of random, four-quadrant biopsy (i.e. systematic biopsy) in Barrett's oesophagus surveillance has been questioned given its drawbacks and the emergence of high-resolution endoscopy and advanced imaging modalities. Our study aims to assess whether neoplastic pathology is typically diagnosed in routine clinical practice by random, four-quadrant or targeted biopsy whilst using high-resolution endoscopy. Methods: The Nottingham University Hospital Barrett's oesophagus dysplasia database was retrospectively analysed. Endoscopic and histopathologic data pertaining to the initial endoscopy in which pathology was diagnosed was extracted from the medical records. The most advanced histopathologic abnormality at initial diagnosis and within twelve months were noted. The corresponding endoscopic impression at initial diagnosis was used to group cases per type of biopsy – random, four-quadrant or targeted. Pearson's χ 2 test of independence was used to analyse the relationship between the type of biopsy and diagnosis, indication for endoscopy, endoscopist level and advanced techniques used. Results: Of the 222 patients involved in the study – a higher proportion were diagnosed through random, four-quadrant biopsy (72.97%) than targeted biopsy (27.03%). 90.91% of low-grade dysplasia, 71.43% of high-grade dysplasia and 50% of intramucosal adenocarcinoma cases were diagnosed by random, four-quadrant biopsy. Across all grades of clinicians, patients were typically diagnosed through random, four-quadrant biopsy. However, amongst specialist consultant endoscopists ( n = 10) the proportion was equal. Conclusions: Our findings strongly emphasize the importance of random, four-quadrant biopsy in the detection of not only low-grade dysplasia, but also high-grade dysplasia and early invasive carcinoma as part of Barrett's oesophagus surveillance.